Jual Beli Followers Di Media Sosial Instagram Tentang Transaksi Elektronik Dalam Pandangan Hukum Islam - Syaripudin, Enceng Iip; Badruzzaman, Puad (Jurnal Hukum Ekonomi Syariah, 2022)
Instagram is one type of social media that is currently being embraced by various groups. Instagram has become one of the most popular social media platforms in Indonesia. Whether for personal photos, experiences, or important events, or for business purposes such as "online stores", etc. Therefore, it is important to make a different impression on Instagram, which can be achieved in various ways, one of which is by increasing the number of followers. The advantages of having a large Instagram following in an online store, such as increasing business account ownership. Furthermore, the greatest impact will be felt by Instagram users who utilize their accounts to sell products. With the increasing number of business people using social media users, who are also known as influencers. The purpose of this study is to find out how the practice of buying and selling Instagram followers works, as well as the views of Islamic law on the practice of buying and selling Instagram followers. Thus, this research is expected to be useful for future scholars and can be used as a reference or reference for them. The process of buying and selling followers is part of the product advertising offered by Instagram accounts that sell followers. The concept of a service product can be summarized as the desire to utilize a product (service) that provides the best quality, appearance, and attributes to users.  Keywords: buying and selling, Followers, Social Media, Instagram,